Personality traits, internal communication, leadership styles, organizational culture and employees’ commitment to change in Malaysian large companies - Marchalina, Leonis (2018)
This study examined the influence of personality traits, internal communication and leadership styles on employees’ commitment to change that are moderated by organizational culture. Employees’ commitment to change is important for large companies to sustain in the global economy. Lewin’s Three Step Model underpinned this study which believed the variables that affect the departure from the status quo to the current state. This study utilized the triangulation approach in order to get both broad and in-depth findings. Quantitative data were collected from 294 employees of large companies in various sectors that were listed in the Kuala Lumpur Stock Exchange (KLSE) Malaysia. The research used the simple random sampling and the cross-sectional survey. In order to understand the real situation of the concerns of the individuals on their commitment to change, six participants were interviewed. The key results revealed that personality traits and transformational leadership influence employees’ commitment to change, moderated by the organizational culture. In addition, the real views of the employees’ commitment to change showed that a strong leadership is necessary to enable the employees to undertake change. Interestingly, authentic personality and five senses (i.e. sense of belonging, sense of valuing, sense of believing, sense of urgency, and sense of improving) emerged from the study as natural concerns. This study successfully meets the objectives of discovering the factors that influence employees’ commitment to change through a moderating effect (i.e. organizational culture). Hence, it is hoped that the study contributes to the change management and human resource literature. The originality of the study is the establishment of the instruments and the construction of the theory on employees’ commitment to change, which highlights the importance of transformational leadership and personality traits. Likewise, this study implies that both practitioners and leaders need to review how they could increase employees’ commitment to change based on various personalities, internal communication and leadership approaches.